Pengaruh Dimensi Kepribadian Big Five terhadap Pola Pikir Kewirausahaan Mahasiswa - Farhanaz Safira; Siti Zahreni (Program Studi Bimbingan dan Konseling Islam IAIN Langsa, 2021)
This study was conducted to determine the effect of the big five personality dimensions on the entrepreneurial mind-set. The subjects in the study were 100 university students (38% male, 62% female) with age range of 18-25 Year (M = 20, SD = 1.528). Sampling was done by using proportioned random sampling method. The instrument used is the big five personality dimension scale and the entrepreneurial mind-set scale. The data examined by multiple regression analysis test. The results of data analysis indicated that there was an influence of the big five personality dimensions on the entrepreneurial mind-set (R2 = .58, F (5.94) = 25.98, p = .000). The dimensions of extraversion, openness to experience and conscientiousness have a significant effect on the entrepreneurial mind-set. Future research is expected to be carried out on different subjects to see the consistency of research results.